KEBIJAKAN PENDIDIKAN DI ERA GLOBALISASI - Sudarmi Ismail (AkMen JURNAL ILMIAH, 2008)
Era Gloalisasi represent an condition showing that this world have progressively minimize. We will not again can hide the kobobrokan or wretchedness from an state. That matter is possibility happened by the blessing of progress of technique informatika, where in the world of education expected by an policy from government which can follow the globalization era.